In Vitro synergy of Farnesyltransferase inhibitors in combination with colistin against ESKAPE bacteria - Marian Klose; Lea Weber; Hagen Sjard Bachmann (PLoS ONE, 2025)
The emergence of antibiotic resistance continues to pose a significant global challenge. Drug repurposing, wherein existing therapeutics are evaluated for new applications, offers a promising strategy to address this issue. Farnesyltransferase inhibitors (FTIs), initially developed for cancer therapy, have demonstrated antimicrobial activity against several gram-positive bacteria. This study investigates their activity in combination with colistin against gram-positive and gram-negative bacteria. We focus on key ESKAPE (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species) pathogens while incorporating additional bacterial strains to provide a comprehensive understanding of differential responses and potential dose-dependent synergistic effects. Antimicrobial susceptibility was assessed using broth microdilution, while synergy was evaluated through checkerboard, time-kill, and growth kinetics assays. When combined with sub-inhibitory colistin, FTIs inhibited gram-negative bacterial growth. Tipifarnib exhibited more potent antimicrobial activity against gram-negative strains than lonafarnib. Peptidomimetic FTIs, B581 and FTI-277, inhibited gram-negative bacteria in combination with colistin but had no effect on the gram-positive strains tested. In contrast, alpha-hydroxy farnesyl phosphonic acid, an FPP analog, and bempedoic acid, targeting the mevalonate pathway, showed no antibacterial activity. In addition to their known inhibition of gram-positive bacteria, FTIs exhibited efficacy against gram-negative bacteria, including colistin-resistant Enterobacter cloacae subsp. cloacae, when combined with sub-inhibitory colistin. This might be due to a mechanism distinct from their eukaryotic targets, potentially involving the disruption of multiple biosynthetic pathways. Future studies will focus on elucidating these mechanisms of FTIs and exploring the therapeutic potential of FTI/colistin combinations against ESKAPE and other multidrug-resistant pathogens.